2017
DOI: 10.3390/ijerph14050519
|View full text |Cite
|
Sign up to set email alerts
|

Mercury in Children: Current State on Exposure through Human Biomonitoring Studies

Abstract: Mercury (Hg) in children has multiple exposure sources and the toxicity of Hg compounds depends on exposure routes, dose, timing of exposure, and developmental stage (be it prenatal or postnatal). Over the last decades, Hg was widely recognized as a threat to the children’s health and there have been acknowledgements at the international level of the need of a global policy intervention—like the Minamata treaty—aimed at reducing or preventing Hg exposure and protecting the child health. National human biomonit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 106 publications
(177 reference statements)
0
25
0
Order By: Relevance
“…This value reflected the long-term exposure of mercury, which was relevant to dietary exposure to methylmercury [42]. The mercury concentration in children's urine was 1 µg/L, which was much lower than the health-based guidance values in urine (7 µg/L) [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…This value reflected the long-term exposure of mercury, which was relevant to dietary exposure to methylmercury [42]. The mercury concentration in children's urine was 1 µg/L, which was much lower than the health-based guidance values in urine (7 µg/L) [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…However, Gross Motor deficits are less subject to bias. Thus, while infant H-Hg levels are ostensibly lower than those found amongst adult women, it is important to remember the vulnerability of infants to environmental threats, given their immature immune systems and continuous growth [ 91 , 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nicolescu et al reported lower arithmetic blood Hg concentrations of children with ADHD in Romania (0.1 μg/L), and none of the children had elevated concentrations [73]. National European Surveys and other studies reported geometric mean blood mercury concentrations for many countries in Europe [86]. Our results from Romania are comparable to results from TD children (8–10 years old) in the Czech Republic in 2008 and German TD children (3–14 years old) during 2003–2006, who have geometric mean blood Hg concentrations of 0.45 µg/L and 0.23 µg/L, respectively.…”
Section: Discussionmentioning
confidence: 99%